Exploring the uptake of implant contraceptives among South African young women : a prediction for health communication campaigns - Manthata, Martha Morongwa (My University, 2019)
Globally, over the years, health promotion organisations have developed communication campaigns geared towards addressing most major public health issues with the intention of preventing risky sexual behaviour. Teenage pregnancy is a major health, social, systemic and economic challenge, not only for the basic education sector but also, crucially for national development in general. The use of modern contraceptives, specifically implant contraceptives, has the potential to alleviate unintended teenage pregnancies. Modern contraceptives such as implant contraceptives have proven to be highly effective from 24 hours after insertion up to three years. Theoretically, the Health Belief Model and the Theory of Planned Behaviour have been applied to guide the study. A quantitative, descriptive survey was used in this study, with data collected using questionnaires. Purposive sampling of six secondary schools under the Mankweng Circuit in the Limpopo province where 306 participants were randomly selected was employed. Data were analysed using the SPSS version 26. The study revealed that that 34% of the participants were willing to use the implant contraceptive method based on the benefits found to be associated with the method. However, 66% were not willing to use the method regardless of the benefits found in using the implant contraceptives. In addition, it was found that only 3.9% of the participants were using implant contraceptives as a tool to prevent unintended pregnancies. This study makes a contribution to existing literature on implant contraceptives uptake among young women in South Africa. It would be informative to organisations and the National Department of Health who propose the use of implant contraceptives to stem increasing teenage pregnancies.
Thesis (M. A. (Communication Studies)) -- University of Limpopo, 2019
Keywords: South African young women; Health communication campaigns; Implant contraceptives; Contraceptive drugs, Injectable; Communication in community health services